2004
DOI: 10.1016/s0022-5347(18)38131-x
|View full text |Cite
|
Sign up to set email alerts
|

882: Relationship of Self-Diagnosed Premature Ejaculation to Other Indicators of Male Sexual Function

Abstract: two groups self-reported sexual functioning . Additionally, results will include comparisons over time within and between the two groups and correlations between questionnaires responses and the NPT and color Doppler.CONCLUSIONS: There are marked differences between men presenting with PC and those presenting with primary ED. Sexual function as measured by NPT, color Doppler and questionnaire data will be discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 0 publications
0
7
1
Order By: Relevance
“…The frequency of sexual intercourse was also found in association with PE by Kaplan in 1974, since then low sexual frequency reported to be a risk factor for PE and was reported by other studies. [42][43][44] In this study there was no significant difference between patients with AS and healthy controls in terms of the frequency of sexual frequency, on the contrary, masturbation is significantly higher in patients with AS. Masturbation might serve as an alternative to sexual intercourse in case of sexual dysfunction.…”
Section: Discussioncontrasting
confidence: 51%
“…The frequency of sexual intercourse was also found in association with PE by Kaplan in 1974, since then low sexual frequency reported to be a risk factor for PE and was reported by other studies. [42][43][44] In this study there was no significant difference between patients with AS and healthy controls in terms of the frequency of sexual frequency, on the contrary, masturbation is significantly higher in patients with AS. Masturbation might serve as an alternative to sexual intercourse in case of sexual dysfunction.…”
Section: Discussioncontrasting
confidence: 51%
“…9,22,42,52 This lack of sexual satisfaction can be detrimental to the overall relationship with their partner. Recently, McCullough et al 52 reported the results of 1158 men responding to a sexual health survey.…”
Section: Risk Factors For Pementioning
confidence: 99%
“…9,22,42,52 This lack of sexual satisfaction can be detrimental to the overall relationship with their partner. Recently, McCullough et al 52 reported the results of 1158 men responding to a sexual health survey. The authors found that men with PE were significantly more likely to report low satisfaction with their sexual relationship, low satisfaction with sexual intercourse and difficulty relaxing during intercourse.…”
Section: Risk Factors For Pementioning
confidence: 99%
See 2 more Smart Citations